PENGARUH LEADER-MEMBER EXCHANGE TERHADAP KINERJA KARYAWAN MELALUI PERAN VARIABEL MEDIASI WORK ENGAGEMENT PADA PT. PERUSAHAAN LISTRIK NEGARA (PERSERO) AREA BENGKULU - Sely Justina; Sugeng Susetyo; Paulus Kananlua (Management Insight: Jurnal Ilmiah Manajemen, 2019)
Work Engagement is a partial mediator between Leader-Member Exchange and employee performance, so that employees with high Leader-Member Exchange and Work Engagement can develop further contribute to employee performance and advance through Work Engagement performance. The purpose of this study was to examines the effect of Leader-Member Exchange on performance with Work Engagement as a mediating variable at the PT. PLN (Persero) Bengkulu Area. The number of samples taken as many as 69 employees in . PLN (Persero) Bengkulu Area. Data obtained by distributing questionnaires were analyzed using mediated regression analysis. It was found that Leader-Member Exchange is positively effect Work Engagement, Leader-Member Exchange has positively impact on employee performance, Work Engagement has positively impact employee performance, and Work Engagement mediates the relationship between Leader-Member Exchange and employee performance